A Comparative Study on Heterogeneity of Clay Rocks Using Pore‐Scale Diffusion Simulations and Experiments. Issue 12 (14th December 2022) - Yuan, Tao; Yang, Yuankai; Ait‐Mouheb, Naila; Deissmann, Guido; Fischer, Cornelius; Stumpf, Thorsten; Bosbach, Dirk
Abstract: Accurate modeling and simulation of radionuclide migration in clay rocks such as the Opalinus Clay (OPA) play a key role in the safety assessment of deep geological repositories for nuclear wastes. At the continuum scale, the representative elementary volume (REV) is a fundamental constraint to quantify the effective diffusivity, which is a key parameter in reactive transport (RT) models. Therefore, an accurate estimation of the REV is essential for a meaningful continuum‐scale RT simulation in heterogeneous clay rocks. This study presents a comprehensive analysis of the heterogeneities of porosity and effective diffusivity in clay rocks by using the classical sampling theory and pore‐scale simulations. First, in this study, the two‐dimensional representative elementary area is correlated with the REV for porosity via a characteristic length. Next, it is shown that the REV for diffusivity is larger than the REV for porosity. Moreover, these two REVs can be correlated using Archie's law. In such a way, the REV for diffusivity can be determined by the developed correlations through analyzing two‐dimensional microstructures, thus significantly reducing the computational cost. Finally, the applicability of our approach for clay rocks is validated by experimental data on the diffusion of tritiated water in the heterogeneous sandy facies of OPA. From both the experimental data and the modeling prediction, the REV for diffusivity in the sandy facies of OPA is in the order of cubic centimeters. This study provides critical insights into the diffusion in heterogeneous clay rocks toward an enhanced predictability of radionuclide migration. Plain Language Summary: Contaminant migration in clay rocks is dominated by molecular diffusion due to their low permeability. To accurately simulate this process at the centimeter scale and above, the rocks can be assumed as homogeneous media only if their volume is larger than a critical volume, also known as the representative elementary volume (REV). Therefore, an accurate estimation of this critical volume is necessary for numerical modeling of contaminant migration in clay rocks. Calculating the REV in clay rocks is a major challenge. Therefore, in this study, the REV in clay rocks was systematically investigated, and easy‐to‐use correlations were established for rapid estimation of REV using two‐dimensional micrographs of the rocks. These critical findings contribute to a better understanding of rock microstructures and to improved calculations of contaminant migration in clay rocks. Key Points: A comprehensive study on the representative elementary volume (REV) for diffusive radionuclide transport in heterogeneous clay rocks Development of a method to correlate the 3D REV for diffusivity to the 2D representative elementary area for porosity via Archie's law and a characteristic length Validation of the predicted REV for diffusivity using data from through‐diffusion experiments that confirm the general applicability of the proposed method